Access to the talar dome surface with different surgical approaches. Issue 5 (October 2019) - Malagelada, Francesc; Dalmau-Pastor, Miki; Vega, Jordi; Dega, Raman; Clark, Callum
Highlights: The AL approach allows for exposure of 24% of the talar dome or of zones 3 (completely), 2, 5, and 6 (partially). The AM approach allows for exposure of 25% of the talar dome or of zones 1 (completely), 2, 4, and 5 (partially). The PL approach gives only exposure to 5% of the talar dome, corresponding to zones 9 and 8 (partially). The PM approach allows for exposure of 7% of the talar dome corresponding to zones 7 and 8 (partially). Minimal or no access is achieved for grid zones 4, 5, 6 and 8, requiring the use of osteotomies or modified approaches. Abstract: Background: Access to the talar dome for the treatment of osteochondral lesions (OCLs) can be achieved via several different approaches to the ankle joint. The recent description of an anatomical nine-grid scheme of the talus has proven useful to localise OCLs but no studies have demonstrated which approaches are indicated to access each of these zones. The aim of this study is to demonstrate the access afforded to each zone by each approach. Methods: Four standard soft tissue ankle approaches were performed simultaneously in ten fresh-frozen cadavers (anterolateral — AL, anteromedial — AM, posterolateral — PL, posteromedial — PM). The area of the talus, which was accessible with an instrument perpendicular to the surface was documented for each of the approaches. Using ImageJ software the surface area exposed with each approach was calculated. The talar dome was then divided using a nine-grid scheme and exposure to each zone was documented. Results: The AL, AM, PL and PM approaches allow for exposure of 24%, 25%, 5%, 7% of the talar dome respectively. The AL gives access to zones 3 (completely) and 2, 5, 6 (partially); the AM to zones 1 (completely) and 2, 4, 5 (partially); the PL to zones 9 and 8 (partially); and the PM to zones 7 and 8 (partially). Conclusions: A large area of the talar dome cannot be easily accessed with the use of standard soft tissue approaches (39%). Minimal or no access is achieved for grid zones 4–6 and 8. In those instances careful preoperative planning is necessary and extended exposure can be achieved with the use of osteotomies, section of the ATFL or through modified approaches.